(untitled) (Global Journal of Management and Business Research, 2015)
This paper primarily sought to determine the factors affecting the entrepreneurship development in small and micro agribusiness firms. Primary data from 120 owners/managers of small and micro agribusiness enterprises purposively selected for the study were analysed using descriptive statistics and multiple regression models. Results showed that majority of the owners/ managers of agribusiness were male (73.3%), married (71.6%), belong to cooperative society (85%), have business size of between 1 and 2 million naira worth (68.33%) with mean family size and monthly income of 5.0 and ₦84,833.00 respectively. Results also showed that majority (56.7%) had secondary education and were motivated to start agribusiness (56.2%) because they could not find job. Parameter estimates from multiple regression showed that age, gender, marital status and estimated business size have positive relationship with level of involvement in agribusiness enterprise while Family size and Primary occupation have negative relationship. Secondary occupation, membership of Cooperative and educational attainment were not significantly related with level of involvement in agribusiness enterprise development. The paper recommended among others effective and adequate entrepreneurship policies such as price stabilization policy and programmes for addressing factors that hinder the growth and development of agribusiness entrepreneurship as a way of actualising the current transformation agenda and "beyond oil" mantra of the present government of Lagos State on poverty eradication.